Basal cell carcinoma arising from an epidermal naevus - Fazarina Mohammed,; Azahsyahrina A,; Moonyza A,; Lee, BR (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Epidermal naevus is a congenital cutaneous hamartoma with a benign course. We highlight a rare case of epidermal naevus with concurrent basal cell carcinoma. A 79-year-old male had a skin biopsy at our centre for an enlarging skin nodule within a linear papular lesion measuring 2 x 4 cm at the left side of his neck, which was later diagnosed as basal cell carcinoma arising from an epidermal naevus. PIK3CA mutation is attributed to basal cell carcinoma which suggests the basal cell carcinoma component is independent of the epidermal naevus component. Clinicians and pathologists must be aware of possible malignant changes that might arise in an epidermal naevus.